2019
DOI: 10.26434/chemrxiv.8859422.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient Copper Catalyzed Multi-component Synthesis of N-acyl amidines via Acyl Nitrenes

Abstract: Direct synthetic routes to amidines are desired, as they are widely present in many biologically active compounds and organometallic complexes. N-Acyl amidines in particular can be used as a starting material for the synthesis of heterocycles and have several other applications. Here, we describe a fast and practical copper catalyzed 3-component reaction of aryl acetylenes, amines and easily accessible 1,4,2-dioxazol-5-ones to N-acyl amidines, generating CO<sub>2</sub> as the only by-product. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…3 Moreover, recent work has shown that intermingling them to experimental investigations is a very powerful approach. 4,5 In the present work, we have used this approach to try to understand the mechanism of formation of amidines through a multicomponent reaction associating a hydrocarbon, a nitrile and an amine delivered as a nitrene.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Moreover, recent work has shown that intermingling them to experimental investigations is a very powerful approach. 4,5 In the present work, we have used this approach to try to understand the mechanism of formation of amidines through a multicomponent reaction associating a hydrocarbon, a nitrile and an amine delivered as a nitrene.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 As a matter of fact, 2 the amidine function allows to form strong ionic or H-bond interactions or to chelate transition metals which has led to its inclusion in many enzyme substrates or inhibitors. 9,10 This strong interest motivates continuous efforts to design new synthetic routes to a large panel of amidine derivatives, especially sulfonyl- [11][12][13][14] and acyl- 5,15 amidines. Amidine syntheses have been devised from many functional groups (amides and thioamides, isonitriles) 16 but more generally amidines are accessible from condensation of primary amines with electrondeficient nitriles 16,17 (or acetals).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, a copper(I)-catalyzed synthesis of N -acyl amidines using dioxazolones was unveiled by de Bruin and co-workers (Scheme 2 ). 17 The reaction protocol initially resulted in an N -acyl copper nitrene intermediate that inserted into a [Cu]–C(sp) bond with subsequent formation of an N -allenyl amide after protodemetalation. The target N -acyl amidines were finally formed after the addition of an amine.…”
mentioning
confidence: 99%